Rebuilding children's lives through education in Uganda - UNICEF (Kampala : UNICEF, 2007)
The go to school, back to school, stay in school (GBS) campaign was launched in North & Northeast Uganda in February 2007.
Impact of the conflict in northern Uganda on going to school
Keywords: Education, Elementary; Children -- Services for -- Uganda